2019
DOI: 10.1371/journal.pone.0225211
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced computed tomography findings of canine primary renal tumors including renal cell carcinoma, lymphoma, and hemangiosarcoma

Abstract: In veterinary medicine, abdominal ultrasonography is used to rank the differential diagnosis of renal lesions. However, a conventional sonographic examination may show nonspecific findings. The purpose of this study was to assess the computed tomography (CT) findings of canine renal tumors, including renal cell carcinoma (RCC), lymphoma, and hemangiosarcoma (HSA). In this retrospective study, the following CT parameters were recorded for each dog: 1) extent of renal involvement of tumors, 2) enhancement patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
2
10
0
1
Order By: Relevance
“…12 Although no significant differences were found between CT and histopathological findings and further studies are needed, renal lymphoma showed homogeneous enhancement, bilateral involvement and multiples masses, while renal cell carcinoma and hemangiosarcomas tended to show heterogeneous enhancement and unilateral renal involvement. 12 In our case, the CT study revealed a large, irregular soft tissue expansile mass within the cranial pole of the right kidney with homogeneous enhancement, hypodense compared with the adjacent normal renal tissue, in agreement with previous studies in humans and dogs. 8,12 In humans this finding is attributed to the fact that the lymphomatous tissue enhances less than the normal renal parenchyma, which helps to differentiate it from squamous cell carcinoma, which usually enhances in the arterial phase.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…12 Although no significant differences were found between CT and histopathological findings and further studies are needed, renal lymphoma showed homogeneous enhancement, bilateral involvement and multiples masses, while renal cell carcinoma and hemangiosarcomas tended to show heterogeneous enhancement and unilateral renal involvement. 12 In our case, the CT study revealed a large, irregular soft tissue expansile mass within the cranial pole of the right kidney with homogeneous enhancement, hypodense compared with the adjacent normal renal tissue, in agreement with previous studies in humans and dogs. 8,12 In humans this finding is attributed to the fact that the lymphomatous tissue enhances less than the normal renal parenchyma, which helps to differentiate it from squamous cell carcinoma, which usually enhances in the arterial phase.…”
Section: Discussionmentioning
confidence: 70%
“…Multi‐phase contrast‐enhanced CT is used in dogs to assess pathologies affecting the kidney 18 while in humans, in addition to CT, MRI is also used for the evaluation of renal tumours in order to reduce the incidence of complications that may appear after a renal biopsy 19 . In a recent retrospective study, the tomographic findings of different canine kidney tumours were evaluated 12 . Although no significant differences were found between CT and histopathological findings and further studies are needed, renal lymphoma showed homogeneous enhancement, bilateral involvement and multiples masses, while renal cell carcinoma and hemangiosarcomas tended to show heterogeneous enhancement and unilateral renal involvement 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Вважають, що значне збільшення розмірів лімфатичних вузлів, їх округлості, Solbiati-індексу (SI), співвідношення між короткою віссю і довжиною лімфатичного вузла (S/L) та гіпоехогенні зміни в лімфатичних вузлах у собак із злоякісною лімфомою стають показовими параметрами злоякісності. Дослідники подають ультрасонографічні характеристики ниркової лімфоми собак, критерії диференціювання пухлинних і непухлинних уражень (Taylor et al, 2014;McAloney et al, 2018;Tanaka et al, 2019). Останнім часом у медичній і ветеринарній онкології дискутується можливість заміни біопсії сучасними методами діагностичної візуалізації: ультразвукове дослідження з контрастним підсиленням; комп'ютерна томографія; позитронно-емісійна томографія; магнітнорезонансна томографія (Škor, 2019).…”
Section: діагностикаunclassified